Hutan Mangrove di Yenanas, Pulau Batanta, Kabupaten Raja Ampat, Propinsi Papua Barat - Suhardjono, Suhardjono (JURNAL BIOLOGI INDONESIA, 2014)
A reseach on mangrove vegetation has been conducted in Yenanas, Batanta Island, Raja Ampat Distric, PapuaBarat Province. The results showed that the diversity of mangrove in Kalitoko was relatively high. About 78 speciesof mangrove (61 genera and 42 families) has been recorded among them, 27 species were classified as rare speciesbased on IUCN list with status VU and CR. The result of vegetation analysis analysis of six transect which cover8,200 m2 of mangrove forest in this location recorded 10 species of mangrove plants with level density was 834-1,244 individual/ha and its basal area was 35.38-123.53 m2/ha. For the sapling the density was 440-1,714individual/ha and its basal area 1.48-4.93 m2/ha. While the seedling density up to 86,364-222,500 individual/ha.Key word : Mangrove Forest, Yenanas, Batanta Island, Raja Ampat Distric, Papua Barat Province